Thermal and Mechanical Properties of Natural Fiber-Reinforced Polymer Composites for Structural Applications - Andi Haslinah; Ikhsan Pangestu (Science Journal Get Press, 2026)
This study systematically investigates the thermal and mechanical properties of seven natural fiber-reinforced polymer composites   jute, kenaf, sisal, bamboo, flax, coir, and hemp  incorporated into epoxy, polyester, and polypropylene matrices at 30 wt% fiber loading. Composites were fabricated via hand lay-up and compression molding, with fiber surfaces treated using alkali (NaOH) to improve fiber–matrix adhesion. Bamboo/epoxy composites achieved the highest tensile strength (201.3 MPa) and glass transition temperature (Tg = 147.8°C), reflecting improvements of 194% and 25% over neat epoxy, respectively. NaOH treatment significantly reduced fiber pull-out and void content, confirming improved interfacial bonding. All composites reduced the coefficient of thermal expansion by 32–55% relative to neat epoxy, enhancing dimensional stability. These findings position bamboo/epoxy and jute/epoxy composites as viable eco-friendly alternatives for lightweight non-primary structural components in building, automotive, and transportation applications.